Recent Advance in Antiobesity Herbs - Jain, Deepak (International Journal of Pharmaceutical & Biological Archive, 2017)
Obesity and its associated disorders are a growing epidemic across the world. Many genetic, physiological, and behavioral factors play a role in the etiology of obesity. It is being characterized by high cholesterol, fatty acid levels, Insulin desensitization; high blood pressure; and excessive adipose mass accumulation. Currently more than 1 billion adults are overweight and at least 300 million of them are clinically obese. It is defined by body mass index and further evaluated by both percentage body tat and total body fat. Diet and exercise are known to play a valuable role in the treatment and prevention of obesity and associated disorders such as hypertension, heart disease, retinopathy, neuropathy, cancer and diabetes. Various factors modulating the development of obesity are age, sex, smoking, growth hormone level, skeletal muscle metabolism. Therefore, the purpose of this review is to examine the prevalence, etiology, consequences, and treatment of obesity.